Analisis Kemandirian Belajar Mahasiswa Program Studi Pendidikan Matematika Sekolah Tinggi Keguruan dan Ilmu Pendidikan Singkawang - Rien Anitra (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: The research aims to describe the students’ self-regulated learning levels in the mathematics education program at STKIP Singkawang. The subjects of this research were all students at second-semester Mathematics Education STKIP Singkawang academic year 2015/2016 as many as 73 students. Data collection used was taken by a questionnaire. Data analysis techniques performed using the quantitative descriptive method by percentage, determine the level of student self-regulated learning used descriptive analysis technique with ideal criteria that is ideal mean an ideal standard deviation. Research result shows: 1) In terms of self-monitoring, the level of student self-regulated learning is 19% very high, 78% high, and 3% sufficient, nothing included low levels; 2) in terms of self-instruction, the level of student self-regulated learning is 16% very high level, 77% higher, and 7% adequate, nothing included low levels; 3) in terms of self-reinforcement, the level of student self-regulated learning is 3% very high, 86% higher, and 11% adequate, nothing included low levels; 4) the level of self-regulated learning showed 5% of students who have a very high level of self-regulated learning, 92% higher, and 3% adequate, nothing included low levels of learning self-regulated learning.